Physical Education and Health Teacher Performance Evaluation Instrument - Mardius, Ali; Rahmalia, Apriyanti; Kumar, Alfiqroam; Khairi, Ashabul; Enjoni; Armen, Meiriani; Hidayat, Fajar Akbar (Indonesian Journal of Sport Management, 2025)
The purpose of this study is to develop a valid, practical, and effective teacher performance evaluation instrument based on professional, personality, and social aspects. This research is a research and development (R&D) study. The model development stages consist of preliminary research, prototyping, expert assessment, content validity estimation using Aiken's V-Coefficient, and inter-observer reliability testing. The practicality and effectiveness testing involved 82 physical education, sports, and health teachers in Padang City. Data analysis was conducted using SPSS 25 statistical software. The results of the data analysis confirmed that the designed instrument has met the criteria for high validity and reliability, making it suitable for use as a measuring tool for the professional performance of physical education, sports, and health teachers. This instrument was developed through systematic stages, starting from literature study, needs analysis, preparation of performance indicators, to field trials involving experts and education practitioners. With this instrument, it is hoped that the process of evaluating the performance of physical education, sports, and health teachers will be more objective, transparent, and can encourage continuous improvement in the quality of learning.